Going Beyond the Literal: a Longitudinal Study of Metaphorical Conceptualization in Sustainability Reports (Global Journal of Human-Social Science, 2023)
Abstract not found
Keywords: conceptual metaphor theory; ontological metaphor; orientational metaphor; structural metaphor; sustainability